2014
DOI: 10.1097/cad.0000000000000062
|View full text |Cite
|
Sign up to set email alerts
|

Can in-vitro chemoresponse assays help find new treatment regimens for malignant gliomas?

Abstract: Various in-vitro chemosensitivity and resistance assays (CSRAs) have been demonstrated to be helpful decision aids for non-neurological tumors. Here, we evaluated the performance characteristics of two CSRAs for glioblastoma (GB) cells. The chemoresponse of fresh GB cells from 30 patients was studied in vitro using the ATP tumor chemoresponse assay and the chemotherapy resistance assay (CTR-Test). Both assay platforms provided comparable results. Of seven different chemotherapeutic drugs and drug combinations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 41 publications
0
3
0
2
Order By: Relevance
“…Уменьшение АТФ указывает на лекарственную чувствительность, а отсутствие снижения -на устойчивость к химиопрепаратам. Этот анализ пригоден для измерения выживаемости культур с низкой плотностью клеток [47,48,49,50,51,52]. Используя данный тест, корейские ученые оценили in vitro чувствительность к гемцитабину первичных культур клеток рака поджелудочной железы и обнаружили достоверную корреляцию между химиочувствительностью и возникновением раннего рецидива у 57 пациентов после хирургической резекции и адъювантной химиотерапии.…”
Section: методы оценки химиочувствительности опухолевых клеток с испоunclassified
See 1 more Smart Citation
“…Уменьшение АТФ указывает на лекарственную чувствительность, а отсутствие снижения -на устойчивость к химиопрепаратам. Этот анализ пригоден для измерения выживаемости культур с низкой плотностью клеток [47,48,49,50,51,52]. Используя данный тест, корейские ученые оценили in vitro чувствительность к гемцитабину первичных культур клеток рака поджелудочной железы и обнаружили достоверную корреляцию между химиочувствительностью и возникновением раннего рецидива у 57 пациентов после хирургической резекции и адъювантной химиотерапии.…”
Section: методы оценки химиочувствительности опухолевых клеток с испоunclassified
“…Одни авторы показали преимущества методов индивидуального определения химиочувствительности перед стандартной химиотерапией, и, опираясь на высокую корреляцию ответов на культурах клеток с клиническими (реакция опухолей, состояние пациентов, протяженность периодов безрецидивной и общей выживаемости), высказались в поддержку развития методов [16,25,47,50]. Другие исследователи не смогли выявить преимуществ методов инди-видуальной оценки химиочувствительности перед протокольными, и заняли отрицательную позицию [19,49,51,82,130]. Третьи ученые выявили лишь частичные преимущества в персонифицированном тестировании восприимчивости неопластических клеток к химиопрепаратам и заняли промежуточную позицию [25,49].…”
Section: заключениеunclassified
“…The grouping of the patients into drug resistance profiles is also unclear and may have been a result of an otherwise small sample size . The CTR‐Test also uses this technology and in a small study with patient‐derived tissue from glioma tumors found a good fit of resistance as measured in the test with clinical resistance in 11 patients …”
Section: The Functional Approach: Chemoresponse Assaysmentioning
confidence: 99%
“…The grouping of the patients into drug resistance profiles is also unclear and may have been a result of an otherwise small sample size [155]. The CTR-Test also uses this technology and in a small study with patient-derived tissue from glioma tumors found a good fit of resistance as measured in the test with clinical resistance in 11 patients [156] In contrast to the EDR, the Adenosine triphosphate (ATP) readout method measures luminescence of intra-cellular ATP as a surrogate marker for drug sensitivity. Assays using this readout method make up a large proportion of publications studying chemoresponse assays.…”
Section: The Functional Approach: Chemoresponse Assaysmentioning
confidence: 99%
See 1 more Smart Citation